Integrating Technology in Remote Arabic Language Education: Opportunities and Challenges - Munapi; Muhammad Faikhel Abdurrahman; M Irsyadul Ibad; Fadhel Mubarak (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2025)
This study explores the integration of digital technology into remote Arabic language education, with a specific focus on formal educational institutions in Southeast Asia. Drawing upon a qualitative descriptive methodology, the research investigates both the opportunities and challenges associated with virtual Arabic instruction in Indonesia and Malaysia. The findings indicate that technology enhances learner engagement, vocabulary acquisition, and access to authentic Arabic content, particularly through tools such as Zoom, Google Classroom, and E-campus. Moreover, student-centered approaches enabled by digital platforms increase confidence and autonomy, especially among introverted learners. However, several obstacles persist, including limited infrastructure, disparities in internet access, lack of teacher training in digital pedagogy, and difficulties in delivering grammar instruction effectively in online environments. These challenges underscore the need for adaptive learning models that address affective, cognitive, and technological aspects of language acquisition. The study contributes to the growing body of Arabic language pedagogy by offering region-specific insights and highlighting the importance of context-sensitive, inclusive, and flexible instructional strategies in the era of digital transformation.